Migrations of Population and the Results in Peripheral Regions (on the Example of Lubelskie Voivodship) - Wesołowska, Monika (Regional Barometer. Analyses & Prognoses, 2011)
In the article, migration movement in Lubelskie Voivodship was presented. Due to the location, the area of the province was treated as a peripheral region. Some consequences of migrations, seen both in social and economic sphere, were also emphasized.